Pendampingan Pembuatan Produk Jamu Herbal Masyarakat Desa Keleyan Kabupaten Bangkalan - Sri Wahyuningsih (Jurnal Ilmiah Pangabdhi, 2021)
During the Covid-19 pandemic since March 2019 in Indonesia, many parties must always be vigilant about the spread of this deadly virus, because many health workers and patients have died and its development continues to increase positively. While a cure for this deadly virus has not been found to date, prevention is preferable. The method of implementation carried out is that the author and the residents of Keleyan village, Socah sub-district, Bangkalan regency make herbal jamu under the brand "Jarai Shaman" ginger, lemongrass, honey and turmeric which is very useful for maintaining stamina in the face of the Covid-19 pandemic. face by paying attention to health protocols and sharing videos about the process of making this herbal “jarai dukun” in the WAG group of the Keleyan village community and youtube. Besides being able to be consumed, the herbal jamu "jarai dukun" can also be used as a micro business for the Keleyan community, Socah sub-district, Bangkalan regency as a local wisdom for Madura.